A Test of the Free Cash Flow Hypothesis: Results from the Petroleum Industry - Griffin, James M. (The Review of Economics and Statistics, 1988)
Over the period 1979-85, the petroleum industry offers a unique test of the agency theory of corporat e restructuring. A panel data set for twenty-five firms indicates con siderable support for a hybrid free cash flow model in which explorat ion expenditures appear guided by neoclassical profitability measures , but at the margin, cash flow also exerts an independent influence. The magnitude of the parameter estimates suggests that the free cash flow hypothesis does not fully explain the gains from restructuring. Copyright 1988 by MIT Press.